(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
We report in this paper Photoionization data of the Rb\(^2+\) ions. Rydberg series of resonances due to \(4p→ nd\) transitions from the \(^2\)P\(^°_3/2\) ground state and the \(^2\)P\(^°_1/2\) metastable state of Rb\(^2+\) converging to the \(4s^24p^4\) \((^1D_2)\) series limit in Rb\(^3+\) are considered. Calculations are performed in the framework of the Screening Constant by Unit Nuclear Charge (SCUNC) formalism and accurate data are tabulated up to \(n=40\). It is shown that the SCUNC analytical formulas reproduce with an excellent precision, recent ALS measurements of Macaluso et al. [J. Phys. B: At. Mol. Opt. Phys. 50 (2017)]. New data are tabulated for \(n = 25\)-\(40\).